A novel design method of the dividing header configuration using 3D numerical simulation for a heat exchanger with a parallel arrangement. (August 2019) - Kim, Sangjo
Graphical abstract: Highlights: A tubular heat exchanger with parallel flow is consider in this study. A novel method is proposed for quickly designing the header configuration. An explicit optimization algorithm and 3D CFD analysis method are employed. Heat transfer for the optimized model is improved as 7.80% compared with base model. Abstract: The header design can play an important role in addressing the issue of the performance of a tubular heat exchanger. In many previous researches, theoretical correlations or optimization techniques with surrogate models has been commonly used for the header design. In this paper, a novel method is proposed for quickly designing the header configuration using an explicit optimization algorithm and a three-dimensional computational fluid dynamic (3D CFD) method. The proposed optimization algorithm was validated by testing benchmark functions. In the optimization, the design variables were coordinate points defining the dividing header configuration, the number of coordinate points was same as the number of tubes. The objective function was the flow uniformity of the heat exchanger. The result was compared with the comparable theoretical design of header configurations. The results indicated that the uniformity was higher for optimized than for theoretical header configurations. Moreover, the heat transfer per one tube row for the optimized model was improved as 7.80% compared with the base model. The main reason for this was that the surface heat transfer coefficient was increased by 7.81% due to reducing flow non-uniformity each tube. Another important finding was that the number of iterations for optimization was small enough to use directly in actual design procedure. The proposed method was confirmed for applications to improve the performance of various heat exchangers with parallel headers.